Five minutes' peace - Murphy, Jill. (New York : Penguin Putnam Books for Young Readers, 1999)
Mrs. Large tries to take a peaceful, relaxing bath but her family has other ideas.
"PaperStar.".
Previously published: New York : Putnam's Sons, 1986.
3.6
K-3
Keywords: Elephants -- Juvenile fiction; Families -- Juvenile fiction; Mothers -- Juvenile fiction; Elephants -- Fiction; Family life -- Fiction; Humorous stories; Mothers -- Fiction; Elephants -- Fiction; Family life -- Fiction; Humorous fiction; Mothers -- Fiction